2014
DOI: 10.3402/ijch.v73.25062
|View full text |Cite
|
Sign up to set email alerts
|

Bioethical issues of preventing hereditary diseases with late onset in the Sakha Republic (Yakutia)

Abstract: BackgroundPrenatal diagnosis of congenital and hereditary diseases is a priority for the development of medical technologies in Russia. However, there are not many published research results on bioethical issues of prenatal DNA testing.ObjectiveThe main goal of the article is to describe some of the bioethical aspects of prenatal DNA diagnosis of hereditary diseases with late onset in genetic counselling practice in the Sakha Republic (Yakutia) – a far north-eastern region of Russia.MethodsThe methods used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Annual SCA1 prevalence rate almost doubled during the study period, reaching current levels of 46–48 cases per 100,000. Analysis of the multi-year trend showed a significant increase in the SCA1 prevalence between 1994 and 2003 (Mann-Kendall test, Sen’s slope + 2.37 [CI 2.15–1.71], p value <0.0001), with stabilization after 2004 likely resulting from intensive genetic counseling efforts [14]. …”
Section: Resultsmentioning
confidence: 99%
“…Annual SCA1 prevalence rate almost doubled during the study period, reaching current levels of 46–48 cases per 100,000. Analysis of the multi-year trend showed a significant increase in the SCA1 prevalence between 1994 and 2003 (Mann-Kendall test, Sen’s slope + 2.37 [CI 2.15–1.71], p value <0.0001), with stabilization after 2004 likely resulting from intensive genetic counseling efforts [14]. …”
Section: Resultsmentioning
confidence: 99%
“…At present, around 30 monogenic hereditary diseases are available for molecular-genetic diagnostics and that number will probably increase in the future. Concurrently, bioethics research was conducted in the field of using DNA testing in the republic [21] that included ethical issues of prenatal diagnostics for late-onset disorders [22].…”
Section: Introductionmentioning
confidence: 99%
“…We follow the principle of the "right to not know" when testing for late onset diseases. The ethical issues of prenatal diagnosis for SCA1 are described in more detail [22].…”
Section: Introductionmentioning
confidence: 99%
“…pregnancies. 17 The UK Huntington s Disease Predictive Testing Consortium (HDPTC) was created in 1989 and collates anonymous data on predictive and prenatal testing for HD across the UK. The HDPTC identified that 21 of 202 high-risk pregnancies were continued 18 .…”
Section: Introductionmentioning
confidence: 99%